Svalbard on the (Post-) Soviet Screen - Rogatchevski, Andrei (Nordlit, 2020)
A selection of Soviet/Russian and Norwegian documentary and feature films about Svalbard is analysed to account for the recurrent issues raised in cinematic representations of the archipelago. Such issues primarily include Svalbard’s ownership and demilitarization, as well as the role that women – and Russia – play in the region. The subject of these representations’ verisimilitude is also discussed. The article concludes that both film groups show a mutually observed parallel reality.